2018
DOI: 10.1111/imj.13808
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to medication, glycaemic control and hospital attendance in young adults with type 2 diabetes

Abstract: Type 2 diabetes is becoming common among people in their 20s and 30s. Glycaemic control is suboptimal in this group and is associated with poor medication adherence. We studied medication adherence over a 24-month period in all diabetes clinic registrants (n = 266) between the ages of 18 and 39 years. We reviewed their glycaemic control using mean HbA1c over the study period and examined hospital records to determine the number of hospital attendances during this time. We found that less than half the group (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
(45 reference statements)
0
9
0
1
Order By: Relevance
“…Further research would be required to establish why younger pregnant women were more likely to stop their antidepressant in early pregnancy. Other New Zealand studies have shown lower adherence to medicine in younger people, 36,37 but it would be useful to see if pregnant women, particularly younger ones, were engaging in psychosocial therapies instead. Determining engagement with non-pharmacological interventions in pregnancy would be informative, as there is a mismatch between those taking an antidepressant in pregnancy (<5%) and the reported prevalence of depressive symptoms (12%).…”
Section: F I G U R E 3 Antidepressant Exposure Trajectories For Individual Pregnancies Ending In a Delivery And Those Not Ending In A Delmentioning
confidence: 99%
“…Further research would be required to establish why younger pregnant women were more likely to stop their antidepressant in early pregnancy. Other New Zealand studies have shown lower adherence to medicine in younger people, 36,37 but it would be useful to see if pregnant women, particularly younger ones, were engaging in psychosocial therapies instead. Determining engagement with non-pharmacological interventions in pregnancy would be informative, as there is a mismatch between those taking an antidepressant in pregnancy (<5%) and the reported prevalence of depressive symptoms (12%).…”
Section: F I G U R E 3 Antidepressant Exposure Trajectories For Individual Pregnancies Ending In a Delivery And Those Not Ending In A Delmentioning
confidence: 99%
“… 32 In young adults with type 2 diabetes, it has been shown that adherence to antihyperglycemic agents (as judged by prescriptions lodged with community pharmacies) was closely related to glycemic control and risk of hospitalization. 33 Medication dispensing was suboptimal among young people with type 2 diabetes in this study: only 63% had diabetes medications dispensed and nearly a third (31%) of those with severe hyperglycemia (HbA 1c > 100 mmol/mol (≥11.3%)) had not been dispensed any diabetes medication in a 6-month period.…”
Section: Discussionmentioning
confidence: 58%
“…1). Specifically, young adults [18][19][20][21][22][23][24][25][26][27][28][29] had over twice the risk of having poor control compared to older adults (aRR 2.15, 95% CI 1.65-2.79, p < 0.001), Hispanics were 18% more likely to have poor control compared to whites (aRR 1.18, 95% CI 1.01-1.39, p value 0.041), and people without any primary care visits were over twice as likely to have poor control when compared to those who frequently utilized primary care services (aRR 2.72, 95% CI 2.23-3.33, p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we found disparities in diabetes control among subpopulations with SMI, specifically young adults and Hispanics, which is consistent with prior work in the general population. 27,28 This adds to the growing evidence that young adults and minorities with SMI could benefit from enhanced screening and early identification of diabetes. 2,15,16,23 It is possible that these positive health care outcomes may be a direct result of better adherence to diabetes medications.…”
Section: Discussionmentioning
confidence: 99%